a+6b+a+5c=

Simple and best practice solution for a+6b+a+5c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+6b+a+5c= equation:


Simplifying
a + 6b + a + 5c = 0

Reorder the terms:
a + a + 6b + 5c = 0

Combine like terms: a + a = 2a
2a + 6b + 5c = 0

Solving
2a + 6b + 5c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6b' to each side of the equation.
2a + 6b + -6b + 5c = 0 + -6b

Combine like terms: 6b + -6b = 0
2a + 0 + 5c = 0 + -6b
2a + 5c = 0 + -6b
Remove the zero:
2a + 5c = -6b

Add '-5c' to each side of the equation.
2a + 5c + -5c = -6b + -5c

Combine like terms: 5c + -5c = 0
2a + 0 = -6b + -5c
2a = -6b + -5c

Divide each side by '2'.
a = -3b + -2.5c

Simplifying
a = -3b + -2.5c

See similar equations:

| 3[5-3(5-t)]-5=5[3(5t-5)+10]-45 | | s(x)=.5x^2-8x+34 | | 3(y+2)=16*2y | | 2c+19=45 | | b^2x^2-5bx+4=0 | | x-0.7=1.9 | | -(5y+3)-(-4y-8)=2 | | -5p=250 | | 5p=250 | | x=0.2x+40000 | | -6y=-32 | | 5(10-10x)=-5(-4x+4) | | -7y=30 | | -17+20-3=5x | | -8-8p=10-3p | | 2(a-4)=4a-2a+4 | | -5y=25 | | 4x+40+6x=1-8x+3 | | 9+10=1 | | -3x=20 | | 50-3xr=17 | | .5(t+7)=39 | | -4y=-36 | | 2(7-x)=14x+2 | | Z^2=169 | | 33.3(x+6)=7 | | x^2+8x-19=0 | | 7y=-49 | | 2r^2+19r+45=0 | | 4t-8x+2t= | | 3z-1=5-4z | | 23x+7-26x=3-5 |

Equations solver categories